Exploring the role of place attachment in shaping sustainable behaviors toward marine cultural heritage: a case study of Dongmen village in Fujian Province, China - Cai, Wenchao; Shu, Zhangwen; Liu, Yisi (Frontiers in Psychology, 2025)
Local residents’ sustainable behaviors associated with cultural heritage are of paramount importance, however the complexities involved are yet to be disentangled. In this study, the concept of the sustainability of residents’ cultural heritage behaviors based on the theory of place attachment is investigated, with a particular focus on religion-related components, using the case of Dongmen village in Fujian Province, China. An attempt is made to answer how residents’ place attachment affects the sustainability behavior of cultural heritage construction and homebuilding. Based on the theory of place attachment, the sustainability of cultural heritage behavior from the perspective of local residents is employed. It is evident that the residents of Dongmen village make use of local knowledge and indigenous resources, and they proactively use associations of the elderly, faith groups, family networks, and overseas relationships. The results of this research show that the sustainable behaviors of Dongmen village residents toward cultural heritage construction are influenced by their feelings of place attachment, which subsequently influence homeland construction actions that, in turn, shape person–place relationships.